Proton-induced ionization of isolated uracil molecules: a theory/experiment confrontation - Champion, C. (2013)
Proton-induced ionization of RNA-uracil target is here theoretically described by two quantum-mechanical models, namely, a first perturbative one developed within the 1st Born approximation and a second one based on the continuum distorted wave approximation. Comparisons between theory and experiments are reported in terms of differential as well as total cross sections exhibiting a very good agreement for the kinematics here Investigated.